Odontogenic myxoma: ambiguous pathology of anterior maxilla. Issue 8 (25th August 2020) - Bisla, Suman; Gupta, Ambika; Narwal, Anjali; Singh, Virendra
Abstract : Swellings in the anterior maxilla are uncommon and if present can be deemed as paradoxical conundrums presenting diagnostic and therapeutic dilemmas. Odontogenic myxoma is a rare, locally aggressive lesion that is primarily seen affecting the mandibular posterior region in association with an impacted tooth. It is found to be associated with odontogenesis. Treatment is usually surgical, with extent varying from curettage to resection. This report describes a rare case of odontogenic myxoma of the anterior maxilla in a 14-year-old boy, with an emphasis on its epidemiology, clinical presentation, histopathology, diagnosis and treatment planning.